Biallelic CACNA1A mutations cause early onset epileptic encephalopathy with progressive cerebral, cerebellar, and optic nerve atrophy. Issue 8 (2nd June 2016) - Reinson, Karit; Õiglane‐Shlik, Eve; Talvik, Inga; Vaher, Ulvi; Õunapuu, Anne; Ennok, Margus; Teek, Rita; Pajusalu, Sander; Murumets, Ülle; Tomberg, Tiiu; Puusepp, Sanna; Piirsoo, Andres; et al.
Abstract : The CACNA1A gene encodes the transmembrane pore‐forming alpha‐1A subunit of the Cav 2.1 P/Q‐type voltage‐gated calcium channel. Several heterozygous mutations within this gene, including nonsense mutations, missense mutations, and expansion of cytosine‐adenine‐guanine repeats, are known to cause three allelic autosomal dominant conditions—episodic ataxia type 2, familial hemiplegic migraine type 1, and spinocerebellar ataxia type 6. An association with epilepsy and CACNA1A mutations has also been described. However, the link with epileptic encephalopathies has emerged only recently. Here we describe two patients, sister and brother, with compound heterozygous mutations in CACNA1A . Exome sequencing detected biallelic mutations in CACNA1A : A missense mutation c.4315T>A (p.Trp1439Arg) in exon 27, and a seven base pair deletion c.472_478delGCCTTCC (p.Ala158Thrfs*6) in exon 3. Both patients were normal at birth, but developed daily recurrent seizures in early infancy with concomitant extreme muscular hypotonia, hypokinesia, and global developmental delay. The brain MRI images showed progressive cerebral, cerebellar, and optic nerve atrophy. At the age of 5, both patients were blind and bedridden with a profound developmental delay. The elder sister died at that age. Their parents and two siblings were heterozygotes for one of those pathogenic mutations and expressed a milder phenotype. Both of them have intellectual disability and in addition the mother has adult onset cerebellar ataxia with a slowly progressive cerebellar atrophy. Compound heterozygous mutations in the CACNA1A gene presumably cause early onset epileptic encephalopathy, and progressive cerebral, cerebellar and optic nerve atrophy with reduced lifespan. © 2016 Wiley Periodicals, Inc.